Sosialisasi Pemberdayaan UMKM dengan Pendekatan Metode Taguchi pada Perbaikan Kualitas Kerupuk Lipat - Haniza, Haniza; Silviana, Nukhe Andri; Sutrisno, Nos; Munte, Sirmas; Nainggolan, Lorena (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
The tri dharma of higher education is a task and function for every lecturer that must be carried out every semester, and one of these activities is carrying out community service. The Industrial Engineering study program had the opportunity to implement it with MSMEs in making folded crackers in Sentis village, Percut Sei Tuan subdistrict. Based on the data, it was found that the quality of crackers was damaged by 21% per month, causing a decrease in income. This service aims to educate entrepreneurs to improve product quality so that cracker sales can increase and reduce damaged products using the Taguchi method.  From the experimental results, it was found that quality improvements in the form of taste, durability and crispness of crackers could be improved through 3 stages, namely the drying factor for 7 hours (A1), the optimal baking factor for 13 minutes (B1), and the optimal frying factor for 2 minutes (C2). The results of this experiment succeeded in improving the quality of crackers, in line with consumer expectations, and it is hoped that they will be able to restore and increase sales which previously experienced a decline.